Molecular Dynamic Study of Water-Cluster Structure in PFSA and PFIA Ionomers. Issue 12 (1st January 2017) - Atrazhev, Vadim V.; Astakhova, Tatiana Yu.; Sultanov, Vadim I.; Perry, Mike L.; Burlatsky, Sergei F.
Abstract : Molecular-dynamics simulations were used to study the structure of water clusters in different perfluorinated ionomers. The ionomers included in this work were Perfluorosulfonic Acid (PFSA) and Perfluoroimide Acid (PFIA). Different shapes and sizes of water domains in PFSA and PFIA were observed. In PFSA, ionomer water domains have spherical-like shape while water domains have complicated branch structure in PFIA ionomer. The mean water-cluster size for PFSA and PFIA ionomers as a function of water content lie on one universal curve, which indicates that the size of water clusters depends primarily on water content and weakly on ionomer chemistry. In PFSA, almost all hydronium ions are located predominantly close to the water cluster/backbone interface for both large and small values of water content; while in PFIA a relatively large fraction of hydronium ions are distributed within the bulk of the water clusters. A similar distribution of acidic groups was observed in both ionomers. In PFSA ionomer, all sulfonic groups are located in the surface water layer at the distance from 3 Å to 6 Å from the backbone. In PFIA ionomer, approximately 60% of sulfonic groups are located in the surface water layer and 40% of sulfonic groups are immersed into the bulk of water cluster.